Coronavirus Disease 2019 Outcomes Among Recipients of Anti‐CD20 Monoclonal Antibodies for Immune‐Mediated Diseases: A Comparative Cohort Study. Issue 3 (10th December 2021) - Patel, Naomi J.; D'Silva, Kristin M.; Hsu, Tiffany Y‐T.; DiIorio, Michael; Fu, Xiaoqing; Cook, Claire; Prisco, Lauren; Martin, Lily; Vanni, Kathleen M. M.; Zaccardelli, Alessandra; Zhang, Yuqing; Sparks, Jeffrey A.; et al.
Abstract : Objective: Patients with immune‐mediated diseases treated with anti‐CD20 monoclonal antibodies may have worse coronavirus disease 2019 (COVID‐19) outcomes due to impaired humoral immunity, but differences compared with the general population are unknown. Methods: We identified patients with immune‐mediated diseases who received anti‐CD20 monoclonal antibodies within 1 year prior to the index date of polymerase chain reaction–confirmed COVID‐19 between January 31, 2020, and January 31, 2021. General population comparators with COVID‐19 were matched up 5:1 by age, sex, and polymerase chain reaction date. Unadjusted and multivariable adjusted (for age, race, body mass index, and Charlson Comorbidity Index) hazard ratios (HRs) and 95% confidence intervals (CIs) for hospitalization, mechanical ventilation, and death in recipients of anti‐CD20 monoclonal antibodies versus comparators were estimated by using Cox regression. Results: We identified 114 cases patients COVID‐19 who had received anti‐CD20 monoclonal antibodies for immune‐mediated diseases (mean age 55 years, 70% female) and 559 matched comparators with COVID‐19 (mean age 54 years, 70% female). Patients treated with anti‐CD20 monoclonal antibodies had higher mortality (adjusted HR 2.16; 95% CI: 1.03‐4.54) than matched comparators. Risks of hospitalization (adjusted HR 0.88; 95% CI: 0.62‐1.26) and mechanical ventilation use (adjusted HR 0.82; 95% CI: 0.36‐1.87) were similar. Similar trends were seen in analyses according to type of indication (eg, rheumatic or neurologic disease) and duration of anti‐CD20 monoclonal antibody use (<1 or ≥1 year) and after patients with interstitial lung disease, those with cancer, and those on glucocorticoids prior to COVID‐19 diagnosis were excluded. Conclusion: Patients who received anti‐CD20 monoclonal antibodies for immune‐mediated diseases prior to COVID‐19 had higher mortality following COVID‐19 than matched comparators, highlighting the urgent need to mitigate excess risks in recipients of anti‐CD20 monoclonal antibodies during the ongoing pandemic.